Preparing novice teachers to develop basic reading and spelling skills in children. - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2004)
This study examined the word-structure knowledge of novice teachers and the progress of children tutored by a subgroup of the teachers. Teachers' word-structure knowledge was assessed using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Tutored children were assessed on several measures of basic reading and spelling skills. Novice teachers who received word-structure instruction outperformed a comparison group of teachers in word-structure knowledge at post-test. Tutored children improved significantly from pre-test to post-test on all assessments. Teachers' post-test knowledge on the graphophonemic segmentation and irregular words tasks correlated significantly with tutored children's progress in decoding phonetically regular words; error analyses indicated links between teachers' patterns of word-structure knowledge and children's patterns of decoding progress. The study suggests that word-structure knowledge is important to effective teaching of word decoding and underscores the need to include this information in teacher preparation.
92 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Southern Connecticut State University, Department of Special Education and Reading, 501 Crescent Street, New Haven, CT 06515, USA. spearswerl11@southernct.edu
Keywords: *Dyslexia/th [Therapy]; *Education/td [Trends]; *Reading; Adult; Articulation Disorders; Articulation Disorders/rh [Rehabilitation]; Child; Dyslexia; Education; Faculty; Female; Health Knowledge; Attitudes; Practice; Humans; Male; Reading; adult; article; attitude to health; child; dept.sed; dyslexia; education; evaluation; female; human; male; reading; speech disorder; university